2014
DOI: 10.1371/currents.dis.56cf1c5c1b0deae1595a48e294685d2f
|View full text |Cite
|
Sign up to set email alerts
|

Art of Disaster Preparedness in European Union: a Survey on the Health Systems

Abstract: Introduction: Naturally occurring and man-made disasters have been increasing in the world, including Europe, over the past several decades. Health systems are a key part of any community disaster management system. The success of preparedness and prevention depends on the success of activities such as disaster planning, organization and training. The aim of this study is to evaluate health system preparedness for disasters in the 27 European Union member countries. Method: A cross-sectional analysis study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 10 publications
1
28
0
1
Order By: Relevance
“…The use of a validated instrument administered by trained personnel from the relevant areas of expertise lends credibility to this evaluation. With less than 30% of district-level indicators classifiable as acceptably prepared, the level of preparedness in these most vulnerable areas of a disaster prone country is almost half of that reported for locales (28) at very low levels of vulnerability (15). Development of human resources, training and education was second only to health system financing mechanisms in lack of preparedness.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The use of a validated instrument administered by trained personnel from the relevant areas of expertise lends credibility to this evaluation. With less than 30% of district-level indicators classifiable as acceptably prepared, the level of preparedness in these most vulnerable areas of a disaster prone country is almost half of that reported for locales (28) at very low levels of vulnerability (15). Development of human resources, training and education was second only to health system financing mechanisms in lack of preparedness.…”
Section: Discussionmentioning
confidence: 97%
“…Preparedness for natural or manmade, predictable or unpredictable disasters (24) at district management as well secondary and tertiary health care delivery facilities was assessed using indicators documented in the toolkit published by the WHO Regional Office for Europe (EURO) in 2012 (27). Benchmark cutoffs were adopted from previous such assessments in the European Union using the same instrument (28). Analysis of published studies regarding disastrous situations from locales as diverse as the Caribbean, Africa, North America, Europe, Pakistan and Japan has shown that actual experience "supports the content and value of the WHO toolkit" (29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventy percent of the hospitals responded to the questionnaire, from which 68% of the hospitals were in the first group (acceptable), and the highest preparedness was for England, Lithuania, and Luxemburg. The highest level of preparedness relates to information component and the lowest relates to training (29).…”
Section: Discussionmentioning
confidence: 99%
“…Many European countries have adopted a similar approach to hazard management (Djalali et al 2014). France, for example, moved away from a disaster-specific system and adopted a complex risk approach, which aims to prepare the country for an array of multifaceted and often cascading hazards (Renda-Tenali and Mancebo 2009).…”
Section: Disaster Management Leadership and Resiliencementioning
confidence: 99%